Environmental factors impacting work satisfaction and performance for adults with autism spectrum disorders. - Pfeiffer, Beth; Braun, Kerri; Kinnealey, Moya; Matczaka, Maggie Derstine; Polatajko, Helene (Journal of Vocational Rehabilitation, 2017)
BACKGROUND: Individuals with ASD have some of the highest rate of post-graduation unemployment and competitive employment rates are very low. There is substantial research identifying specific person factors influencing employment outcomes, although there is very little research exploring the impact of environmental factors. OBJECTIVE: The purpose of this article is to understand the impact of environmental factors on work satisfaction and performance from the perspective of adults with Autistic Spectrum Disorder (ASD). METHODS: Qualitative interviews were used to gather personal perspectives from working adults with ASD. The data was micro-analyzed for open coding and organized under common categories. When data was saturated, axial coding occurred resulting in multiple categories linked together under a common central theme. RESULTS: Results identified the central category of Facilitators and Barriers of Person and Environment Fit for Work Satisfaction and Performance, which encompassed the categories, subcategories and links between categories. Both environmental factors and person-fit were identified as two overarching categories where barriers and facilitators were present. CONCLUSIONS: Adults with ASD identified that social interactions, attitudes, and the physical or sensory environment impacted perceptions of work satisfaction and performance. Future research is needed to better understand how to reduce environmental barriers in the workplace for adults with ASD.